Диагностика сочетанной хирургической патологии как предиктор уровня симультанных оперативных вмешательств - Завгородний, С. Н.; Кубрак, М. А.; Данилюк, М. Б.; Рылов, А. И.; Завгородній, Сергій Миколайович; Кубрак, Михайло Анатолійович; Данилюк, Михайло Богданович; Рилов, Андрій Іванович; Zavgorodniy, S. M.; Kubrak, M. A.; Danilyk, M. B.; Rylov, A. I. (Українська медична стоматологічна академія, 2019)
Резюме. Основной причиной незначительного количества симультанных операций (5,5 %) является недостаточный уровень выявления сопутствующей хирургической патологии. Цель исследования. Улучшить диагностику сочетанной хирургической патологии у пациентов с заболеваниями эндокринной системы и повысить процент выполнения симультанных оперативных вмешательств путем применения алгоритма обследования данной категории больных. Объект и методы. Согласно разработанного алгоритма диагностики обследовано 318 пациентов. Результаты исследования. У 71 (22,3 %) обнаружено от 1 до 3 сопутствующих хирургических заболевания. 64 (90,1 %) пациентам было произведено симультанное оперативное вмешательство. Выводы. 1. Применение разработанного нами алгоритма диагностики позволяет повысить уровень выявляемости сочетанной патологии до 22,3 %.2. Повышение уровня диагностики сочетанной патологии, путем использования данного алгоритма, позволило у 20,1 % больных выполнить симультанное хирургическое вмешательство без повышения уровня послеоперационных осложнений и летальности. Резюме. Основною причиною незначної кількості симультанних операцій (5,5 %) є недостатній рівень виявлення супутньої хірургічної патології. Мета дослідження. Покращити діагностику поєднаної хірургічної патології у пацієнтів із захворюваннями ендокринної системи і підвищити відсоток виконання симультанних оперативних втручань шляхом застосування алгоритму обстеження даної категорії хворих. Об’єкт і методи. Згідно розробленого алгоритму діагностики обстежено 318 пацієнтів. Результати дослідження. У 71 (22,3%) виявлено від 1 до 3 супутніх хірургічних захворювання. 64 (90,1%) пацієнтам було вироблено симультанне оперативне втручання. Висновки. 1. Застосування розробленого нами алгоритму діагностики дозволяє підвищити рівень виявлення поєднаної патології до 22,3%. 2. Підвищення рівня діагностики поєднаної патології, шляхом використання даного алгоритму, дозволило у 20,1% хворих виконати симультанне хірургічне втручання без підвищення рівня післяопераційних ускладнень і летальності. Abstract. At 20.0 - 30.0% of patients hospitalized in a surgical hospital, there are 2 - 3 concomitant diseases that can be eliminated in an operative way. However, in practice, the percentage of performing simultaneous surgical interventions is only 5.5%. The main reason is the insufficient level of detection of concomitant surgical pathology in this category of patients. The purpose of the study. To improve the diagnosis of combined surgical pathology in patients with endocrine system diseases and to increase the percentage of performing simultaneous surgical interventions by applying an algorithm of examination of this category of patients. Object and methods. According to our algorithm for the diagnosis of combined surgical pathology, 318 patients were enrolled for routine surgery with endocrine organs at the age of 53.3 ± 9.6 years. Results of the study. At 71 (22.3%) patients we found from 1 to 3 concomitant surgical diseases. In the structure of pathology, a combination of thyroid gland pathology and gallstone disease / polyposis of the gallbladder was most often encountered - 35 (49.3%). In 13 (18.3%) the pathology of the parathyroid and thyroid gland was revealed. In 7 (9.9%) - diseases of the thyroid gland and pelvic organs and 5 (7.0%) - adrenal pathology in combination with gallstone disease was revealed. In 3 (3.2%) patients with thyroid disease, concomitant diseases of soft tissues were diagnosed. At 8 (11,3%) - a combination of other pathology. 64 (90.1%) patients underwent simultaneous surgical intervention. In 7 (10.9%) patients in the postoperative period there was transient hypoparathyroidism; in 4 (6.4%) - local nigmoid complications. There were no lethal cases after simultaneous surgical interventions. Conclusions. 1. The level of performed simultaneous surgical interventions directly depends on the detectability of the combined surgical diseases during the examination of the patient. 2. Application of the diagnostic algorithm developed by us makes it possible to increase the detection rate of the combined pathology to 22.3%. 3. An increase in the level of diagnosis of the combined pathology, by using this algorithm, allowed simultaneous simultaneous surgical intervention in 20.1% of patients without an increase in the level of postoperative complications and lethality.
Діагностика поєднаної хірургічної патології як предиктор рівня симультанних оперативних втручань
Diagnostics of combined surgical pathology as a predictor of level of simultaneous operations
Keywords: сочетанная патология; эндокринные заболевания; симультанные операции; диагностика; поєднана патологія; ендокринні захворювання; симультанні операції; діагностика; combined pathology; endocrine diseases; simultaneous operations; diagnostics